HIGH PRESSURE PUMP DAMAGE ANALYSIS MPK MTU 16 V 4000 M 90 SERIES ON KRI PARCHIM CLASS USING SWOT METHOD - Sutrisno Sutrisno; Wawan Kusdiana; Anton Nugroho; Abdul Rahman (JOURNAL ASRO, 2020)
Hasan Basri-382 Indonesian warhip (KRI) use MTU 16 V 4000 M 90 diesel engine with common rail technologythat uses a High Pressure Fuel Pump. The pump has a vital function because it provides fuel up to a pressureof 1400 bars on the common rail. The problem is that there is pump compilation or damage (leakage), then thefuel pressure at the High Pressure Pump input drops and risks the output pressure of the fuel High PressurePump towards the common rail, where the pressure drops dramatically, so that the fuel pressure is below 4 baror fuel pressure inside the common rail below 700 bar Engine Control Unit (ECU) accepts the engine to stop theengine. The price of the pump is too expensive. In addition, this pump cannot be repaired or in other words itmust be replaced by the new one. Based on the pump for life, it must be replaced every 4500 hours or in onceW5 maintenanc period. But this lifetime schedule has never been approved. Therefore, it is expected to causedamage to the pump so prevention efforts can be made. In addition, the author has also used the SWOTmethod to find the best strategy in finding solutions to the problems of this High Pressure Pump. And of course,these strategies are used for advice at the end of this settlement.Keywords: Common Rail, Damage, High Pressure Pump, Parchim Class, and SWOT Method